Redescription of Bomolochus bellones Burmeister, 1835 (Copepoda, Cyclopoida, Bomolochidae) recovered from Cololabis saira (Brevoort, 1856) (Actinopterygii) in Japan, with descriptions of the male and copepodids v-iii of the species. - Izawa, K. (Crustaceana, 2023)
Bomolochus bellones Burmeister, 1835 is redescribed based on specimens recovered from the bucco-branchial cavity of the Pacific saury, Cololabis saira (Actinopterygii, Beloniformes, Scomberesocidae), in Japan. The male, copepodid V female, copepodid IV female, and copepodid III male of the species are described. The postantennal processes and lateral processes have appeared in the female at copepodid V.